2003
DOI: 10.1172/jci200318499
|View full text |Cite
|
Sign up to set email alerts
|

Physiological role for P2X1 receptors in renal microvascular autoregulatory behavior

Abstract: This study tests the hypothesis that P2X 1 receptors mediate pressure-induced afferent arteriolar autoregulatory responses. Afferent arterioles from rats and P2X 1 KO mice were examined using the juxtamedullary nephron technique. Arteriolar diameter was measured in response to step increases in renal perfusion pressure (RPP). Autoregulatory adjustments in diameter were measured before and during P2X receptor blockade with NF279 or A 1 receptor blockade with 1,3-dipropyl-8-cyclopentylxanthine (DPCPX). Acute pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
165
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(180 citation statements)
references
References 47 publications
13
165
2
Order By: Relevance
“…No information is yet available concerning NPPs 1 and 2 in the rat. NTPDase8 has been detected in porcine tubules [21], but its exact location is not yet known induce constriction [40]. However, strong evidence also exists for adenosine (acting via A 1 receptors) being the chemical mediator in this response [41,42].…”
Section: Ntpdase3mentioning
confidence: 99%
“…No information is yet available concerning NPPs 1 and 2 in the rat. NTPDase8 has been detected in porcine tubules [21], but its exact location is not yet known induce constriction [40]. However, strong evidence also exists for adenosine (acting via A 1 receptors) being the chemical mediator in this response [41,42].…”
Section: Ntpdase3mentioning
confidence: 99%
“…Blockade of P2rx1 receptors or deletion of P2rx1 receptors in knockout mice eliminates pressure-mediated afferent arteriolar contraction. 47 In hypertensive renal disease, pathological changes arise in small arteries in the early stage. 48 So, this ATP-P2X axis might be damaged, which could subsequently lead to down regulation of pressure sensory ability and cause glomerular hypertensive injury.…”
Section: Ds-h Ds-l Ds-h-tel Ds-h-mentioning
confidence: 99%
“…Although M3 receptors are linked to a Gq/11/PLC/IP3/Ca 2+ signalling pathway, we hypothesized that in contrast to cardiac muscle, excitation-contraction (E-C) coupling in smooth muscle occurs by Ca 2+ entry through VGCCs, which evokes IP3R-mediated Ca 2+ release via CICR mechanism. This hypothesis needs to be tested in vascular myocytes regulated by ionotropic receptors, which are not coupled to the Gq/11-GTP/PLC/IP3 system.Taking into account the importance of ionotropic P2X receptors (Burnstock, 2007;Surprenant and North, 2009) in the regulation of renal circulation (Malpas and Leonard, 2000;Inscho et al, 2003;Cupples and Braam, 2007;Guan et al, 2007a), we tested our hypothesis on RVSMCs, which, as we have recently demonstrated, express functional monomeric P2X1 and heteromeric P2X1/4 receptors (Harhun et al, 2010). We found that depolarization of RVSMCs following P2X receptor activation induces IP3R-mediated Ca 2+ release from sub-plasmalemmal ('junctional') sarcoplasmic reticulum (jSR), which is activated mainly by Ca 2+ influx through VGCCs.…”
mentioning
confidence: 94%